The role of the lysosomal system in beta amyloid 1-40-mediated neurodegeneration in cultured cortical neurons - McCormack, Róisin Maureen (Trinity College (Dublin, Ireland). Department of Physiology, 2007)
β-amyloid (Aβ1-40) is a component of the senile plaques found in Alzheimer’s disease (AD). There is evidence that Aβ mediates its apoptotic effect through release of lysosomal proteases to the cytosol with subsequent apoptosis. The aim of this study was to investigate the mechanisms of Aβ-mediated regulation of the lysosomal system. Primary cultured rat cortical neurons were treated with fibrillar Aβ1-40 peptide (2μM). To assess the role of p53 in mediating the modulatory effects of Aβ1-40, cells were pretreated with the p53 inhibitor, pifithrin-α (50nM). Aβ1-40 significantly increased phospho-p53 ser15 expression and its transcriptional target, Bax, in a p53-dependent manner. In Aβ-treated cells, there was increased localisation of phospho-p53 ser15 at the lysosome and this was attenuated by pifithrin-α. The increased association of p53 with lysosomes correlated with a destablisation of the lysosomal membrane, as demonstrated by a relocalisation of acridine orange from the lysosomes to cytosol and pifithrin-α reversed the Aβ-induced disruption of lysosomal stability. Aβ evoked a significant reduction in expression of the lysosome associated membrane protein (LAMP-1) as assessed by fluorescence microscopy and western immunoblot, however this was not dependent on p53. Overall, these results provide evidence that Aβ1-40 impacts on p53 leading to destablisation of the lysosomal membrane.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin